Low-Data Cryptanalysis On SKINNY Block Cipher. (2nd February 2022) - Hua, Jialiang; Liu, Tai; Cui, Yulong; Qin, Lingyue; Dong, Xiaoyang; Cui, Huiyong
Abstract: At CRYPTO 2021, Dong et al. proposed an automatic method of Meet-in-the-Middle (MITM) key-recovery attacks. In this paper, we further extend it to a new automatic model which can be used to find low-data complexity attacks. With the help of the automatic model, we propose MITM attacks against reduced-round versions of all the six members of the SKINNY family with extremely low-data complexity. More precisely, we present MITM attacks against 19-round SKINNY -n -3n, 15-round SKINNY -n -2n, 11-round SKINNY -n -n with three, two, one plaintext-ciphertext pairs, separately. In addition, we can attack two more rounds and three more rounds with no more than 2^8 and 2^32 data complexity, respectively.